TOEIC Training and Prediction Test to Improve Student Competency of SMKN 44 Jakarta - Agoestyowati, Redjeki (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
The English language skills of students at State Vocational School 44 Jakarta are very diverse; some are very good, some are pretty good, some are passable, and many are still lacking, so improving English in the school environment is necessary. One indicator that more students are less able to use English to communicate is seen from the TOEIC Prediction Test Score, which has only reached 26.5% for students who got a TOEIC score above 405. Apart from improving competency, this training also aims to determine predicted TOEIC scores and increase English communication skills for SMK Negeri 44 Jakarta students. This activity is carried out as training before taking the TOEIC Prediction Test, which is conducted for 6 hours (3 hours per day). Introductory training about TOEIC and how to do TOEIC questions, which total 200 questions, is an effort to get a TOEIC score above 400. Implementing this activity is carried out by providing training in the form of delivering Listening Comprehension and Reading Comprehension material, discussions, and TOEIC test simulations, including listening and reading skills. Two hundred students of SMK Negeri 44 Jakarta attended this activity. The activity results showed increased knowledge about TOEIC, how to answer TOEIC questions, and student competence in the TOEIC test. It can be seen from the questionnaire distributed after attending the training. The questionnaire results showed an increase in students' knowledge of the TOEIC test with a percentage of 90% and an increase in students' English competence to communicate using English. However, it still needs to be better regarding value or score improvement. The highest TOEIC score from test participants was 890, and the lowest TOEIC score was 60. Of the total 200 students, 53 students got a score above 405 or still only 26.5%, so to get better results, it is recommended that the training time be increased to 10 -12 hours.